Research on the Influence of Social Networks on the Manifestation of Aggression in Adolescents - Shatri Saranda; Thaçi Bujar (Insight: the psychological dimensions of society, 2024)
Teenagers are the most active, and, therewith, the most vulnerable segment of Internet users. The purpose of this study was to examine the relationship between indicators of social network addiction and aggression in adolescents aged 11–14. Methods. The study’s methods were as follows: a survey was distributed to participants to collect information; testing was done using standardized instruments such as “The Buss-Perry Aggression Questionnaire”, the Kimberly Young Internet Addiction Test, and the Problematic Internet Use Scale; and the data was analyzed using rigorous statistical analysis. This included the Student’s t-test, correlation analysis with Pearson coefficient calculations, and the use of the Statista 8.0 analysis platform. Results. A high level of general aggression was identified in the sample examined (22.0% demonstrated a high level). No statistically significant difference was identified in the level of aggression between boys and girls. A significant positive correlation was identified between aggression indicators and the level of Internet addiction. An analysis of the correlation between the level of aggression using social media demonstrated no significant association between these traits in the general population. A positive relationship was identified between aggression and social media use in respondents with high levels of addiction. The connection between Internet addiction and social media addiction manifested itself differently between the sexes: boys demonstrated a more pronounced attachment to the Internet in general, while girls were more dependent on social media communication. Discussion and conclusions. The results demonstrate that there is a correlation between social network addiction and aggression, but it is not linear. Additional factors that contribute to higher levels of aggression in children and young people should be explored. The findings contribute to an understanding of the relationship between social network use and levels of aggression, which is part of the broader problem of the transformation of social relations under the influence of information technology. In practical terms, the data can be used in planning the work of social educators and parents to correct the behaviour and social adaptation of adolescents.